(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Background: Various conditions required arthroplasty of humerus bone like osteoarthritis, Rheumatoid arthritis, and rotator cuff arthropathy etc. Identification of the sex of remains of the human body parts is also important for the forensic anthropologist. So, this study was conducted to measure the upper and lower ends of humerus to help in the reconstruction of the humerus as the joints are often the major region of damage during accidents and to differentiate male and female humerus which will help in identification of remains. Methods: A study is conducted on 95 dry humeri of unknown sex and various parameters are implemented to identify the gender of the humeri. The data is analyzed using SPSS software and an independent T-test was done to compare male and female and right and left parameters. Result: There were 17 parameters that are highly significant between males and females. There were only 3 parameters that were significant on the right and left sides as the P value was